ANALISIS IMPLEMENTASI KEBIJAKAN BANTUAN LANGSUNG TUNAI (BLT) DANA DESA DALAM MENDUKUNG UPAYA PENANGANAN KEMISKINAN DI DESA SIJARANGO I KECAMATAN PAKKAT - Simbolon, Lestari; Sihombing, Natalia E.T; Degodona, L. Primawati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the implementation of the Village Fund Direct Cash Assistance (BLT) policy in supporting poverty alleviation efforts in Sijarango I Village, Pakkat District, Humbang Hasundutan Regency. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the Village Fund BLT has been running in accordance with the established mechanism, starting from the data collection process, verification, to the distribution of assistance. The Village Fund BLT is given to extremely poor families and poor families who meet certain criteria, such as losing their livelihoods, having family members with chronic diseases, or living alone. The Village Fund BLT distribution process is carried out transparently and involves the active participation of village officials, the Village Consultative Body (BPD), and community representatives. The main obstacle faced is the absence of bank accounts for some beneficiaries, so the distribution is carried out in cash. In general, the Village Fund BLT has had a positive impact in helping the community meet basic needs and improve economic welfare.